Chimairacoris flavipes sp. nov., (Hemiptera, Heteroptera, Miridae, Phylinae) from New Caledonia - Taszakowski, Artur; Masłowski, Adrian; Cassis, Gerasimos (Zootaxa, 2023)
A new species, Chimairacoris flavipes Taszakowski & Cassis sp. nov. (Hemiptera, Heteroptera, Miridae, Phylinae), is described from New Caledonia. Habitus and SEM images of the female and necessary morphological structures are presented. The structure of the female genitalia is also shown in detail. An identification key and distributional map of known Chimairacoris species are provided.